Moiré superlattices and 2D electronic properties of graphite/MoS2 heterostructures. (May 2019) - Trainer, Daniel J.; Putilov, Aleksei V.; Wang, Baokai; Lane, Christopher; Saari, Timo; Chang, Tay-Rong; Jeng, Horng-Tay; Lin, Hsin; Xi, Xiaoxing; Nieminen, Jouko; Bansil, Arun; Iavarone, Maria
Abstract: Heterostructures of graphite/MoS2 display a wide range of lattice registry due to rotational alignment and/or lattice mismatch. Using high resolution scanning tunneling microscopy and spectroscopy (STM/STS) we investigated electronic properties of these heterostructures and observed changes in the bandgap as a function of the twist angle between the layers. Green's function based electronic structure calculations were carried out in order to shed light on the mechanism underlying the observed bandgap changes. Indirect coupling between the pz orbitals of the substrate Carbon atoms and the dz2 orbitals of the MoS2 layers (mediated by the pz orbitals of the bottom S layers) is found to be responsible for changes in the valence-band edge. Simple stacking of van der Waals materials with diverse properties have the potential to enable the fabrication of novel materials and device structures with tailored electronic properties. Highlights: MoS2 /HOPG heterostructures produce an array of angle-dependent Moiré patterns. The measured energy band gap is correlated with Moiré periodicity. Coupling of the pz orbitals of Sulphur with Carbon orbitals of the HOPG is responsible for driving changes in the band gap with twist angle.